Korelasi Indeks Prestasi Kumulatif dengan Nilai UKMPPD CBT Periode November 2018 – Agustus 2019 Fakultas Kedokteran Universitas Riau - Rahmat Rezki; Firdaus Firdaus; Enikarmila Asni (Jurnal Ilmu Kedokteran, 2020)
Academic achievement is an indication level of learning effort by someone. One of them is grade point average (GPA). Some researches showed correlation between GPA and medical competency test. This medical competency test consists of two parts: multiple choice question computer-based test (CBT) and an objective structured clinical examination (OSCE). This cross sectional study aimed to determine the correlation of GPA with CBT scores for the period of November 2018 - August 2019 on students of Medical Faculty Riau University. The number of samples in this study were 149 students. GPA assessment were obtained from preclinical and clinical data of GPA. The majority GPA results are included in the value of 2.75-3.49 and have a percentage of 94% (preclinical), 96% (clinical) and 98.7% (combined). CBT score <66 were obtained from 12.8% student while 87,2% students get score ≥ 66. Spearman test showed significant correlation between GPA and CBT scores of students.